Pengaruh Pemanfaatan Teknologi Informasi, Pengetahuan Perpajakan dan Tarif Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi Pengguna E-Commerce di Bekasi - Cahya Kamila, Aulia; Nuryati, Tutty; Rossa, Elia; Puspaningtyas Faeni, Dewi; Manrejo, Sumarno (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Taxes are a coercive contribution from society to the state that is required by laws and regulations and is used to finance government expenditure for the benefit of the people, but the results cannot be measured directly. The aim of this research is to determine the effect of information technology utilization, tax knowledge and tax rates on individual taxpayer compliance. The theory behind this research is attribution theory. This research uses the literature review method. The researcher presents reasons, other explanatory variables, and findings from previous literature. The results of this research are that information technology utilization, tax knowledge and tax rates has a effect of individual taxpayer compliance.